2016
DOI: 10.3389/fphys.2015.00412
|View full text |Cite
|
Sign up to set email alerts
|

Heart Rate Variability in Porcine Progressive Peritonitis-Induced Sepsis

Abstract: Accumulating evidence suggests that heart rate variability (HRV) alterations could serve as an indicator of sepsis progression and outcome, however, the relationships of HRV and major pathophysiological processes of sepsis remain unclear. Therefore, in this experimental study HRV was investigated in a clinically relevant long-term porcine model of severe sepsis/septic shock. HRV was analyzed by several methods and the parameters were correlated with pathophysiological processes of sepsis. In 16 anesthetized, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
29
3
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(41 citation statements)
references
References 53 publications
6
29
3
3
Order By: Relevance
“…There was no premature death due to refractory septic shock; all animals were euthanized according to the original experimental time schedule > 40 h after induction of sepsis. This was very different from our traditional experimental scenario with higher dose of feces, in which refractory septic shock with lethal consequences usually developed within 24 h. 11…”
Section: Resultscontrasting
confidence: 66%
See 2 more Smart Citations
“…There was no premature death due to refractory septic shock; all animals were euthanized according to the original experimental time schedule > 40 h after induction of sepsis. This was very different from our traditional experimental scenario with higher dose of feces, in which refractory septic shock with lethal consequences usually developed within 24 h. 11…”
Section: Resultscontrasting
confidence: 66%
“…Although in none of our previous studies with the porcine peritonitis-induced sepsis model (e.g. Jarkovska et al 11 ) sex-specific differences in the response to the infection were observed, they cannot be completely excluded.…”
Section: Study Limitationsmentioning
confidence: 72%
See 1 more Smart Citation
“…A recent report of a porcine model of septic peritonitis investigated the variations of HRV during septic shock . In this study, HRV was analyzed with various methods throughout the development of progressive hyperdynamic septic shock in 11 anesthetized pigs after inoculation of 1 g/kg of autologous feces into the abdominal cavity.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent experimental study investigating HRV in a porcine model of peritonitis‐induced septic shock, a reduction of the HF component and an increase in both the LF component and LF/HF ratio were observed after the onset of sepsis . These changes in HRV were associated with pronounced parasympathetic inhibition and a shift of sympathovagal balance toward sympathetic cardiac modulation.…”
Section: Introductionmentioning
confidence: 96%